Do informational nudges alter firms' hiring behavior of older workers? - Pia Homrighausen; Julia Lang (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
This paper analyses a local marketing campaign in Germany that provided information about unproven agerelated stereotypes and the value of older workers. The campaign was designed to increase the hiring rate of older workers. Using comprehensive register data, we find that the information provided by the campaign (via banners, interviews, job fairs and information brochures) did change firms' employment behavior. The cheap and mild intervention increased the employment rate of older workers on average by 3 percentage points. This increase, however, is attributable to an increase in job stability rather than to an increase in the hiring of older workers. – – Die Studie analysiert eine Informationskampagne, die zum Ziel hatte, die Vorbehalte von Firmen gegenüber Arbeitnehmern abzubauen und die Bereitschaft, ältere Arbeitslose einzustellen, zu erhöhen. Unsere Ergebnisse auf Basis umfangreicher administrativer Daten zeigen, dass die Informationskampagne, welche u.a. Plakate, Experteninterviews, Informationsbroschüren und Job-messen zum Thema beinhaltete, die Beschäftigungsrate älterer Arbeitnehmer im Durchschnitt um etwa drei Prozentpunkte erhöhte. Der Anstieg in der Beschäftigungsrate Älterer scheint jedoch weniger bedingt durch einen Anstieg der Einstellungsquote, sondern vielmehr durch eine stabilere Beschäftigung älterer Arbeitnehmer.
Keywords: D83; J21; J23; J64; J78; 330; Difference-in-differences; Information; Nudge; Older workers; Stereotypes; Unemployment